Bioelectrical impedance analysis of body composition and survival in patients with heart failure. Issue 1 (4th December 2018) - Thomas, Elizabeth; Gupta, Pritha P.; Fonarow, Gregg C.; Horwich, Tamara B.
Abstract : Background: Studies have shown that higher body mass index (BMI) is associated with improved prognosis in heart failure (HF), and this is often termed the obesity paradox. Hypothesis: Analysis of body composition may reveal that muscle mass rather than adipose tissue accounts for the obesity paradox. Methods: Bioelectrical impedance analysis of body composition in 359 outpatients with HF was performed using an In Body 520 body composition scale (Biospace Inc., California). Body fat and lean mass were indexed by height (m 2 ). The cohort was stratified by median fat and lean mass indexed by height. Results: The mean age of patients studied was 56 ± 14; mean left ventricular ejection fraction was 38 ± 16%. Patients with higher indexed body fat mass had improved 5‐year survival over patients with lower indexed body fat mass (90.2% vs 80.1%, P = 0.008). There was also improved survival in patients with high vs low indexed lean body mass (89.3% vs 80.9%, P = 0.036). On multivariable analysis, higher indexed body fat mass, but not lean body mass, was independently associated with improved survival (HR 0.89, per kg/m 2 increase in indexed body fat mass, P = 0.044); however, this was attenuated after adjustment for diabetes. The combination of low lean with low‐fat mass was independently associated with poor prognosis. Conclusions: Our data suggest that higher fat mass—and to a lesser extent higher lean mass—is associated with improved outcomes in HF. Further investigations of specific components of body composition and outcomes in HF are warranted.